2019
DOI: 10.1177/0170840619844286
|View full text |Cite
|
Sign up to set email alerts
|

Collective Memories as a Vehicle of Fantasy and Identification: Founding stories retold

Abstract: This paper builds on recent calls for a polyphonic approach to study rhetorical uses of the past, to account for multiple and diverse voices that take part in the construction of collective memories. To this end, I explore (multiple) collective memories of a charity’s founding story by tracing how this story was retold in the organization. My findings demonstrate that these recollected stories were localized and embellished within two specific mnemonic communities. I show that two different renditions of the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(69 citation statements)
references
References 69 publications
(131 reference statements)
1
66
0
2
Order By: Relevance
“…This position focuses on retrospective research into how the past is narrated in the present, which has seen substantial interest in recent years (Linde, 2008;Mai, 2015). Suddaby et al (2010) developed the concept of rhetorical histories, which has become influential as a way of understanding the history-making of organizations (Foster et al, 2011(Foster et al, , 2017Oertel and Thommes, 2015;Suddaby et al, 2016). The focus here is on the present, which recounts the past instrumentally in ways that suit current needs and strategies, essentially 'revising the past (while thinking in the future perfect tense)' (Gioia et al, 2002: 622).…”
Section: Retrospective Organizational Memorymentioning
confidence: 99%
“…This position focuses on retrospective research into how the past is narrated in the present, which has seen substantial interest in recent years (Linde, 2008;Mai, 2015). Suddaby et al (2010) developed the concept of rhetorical histories, which has become influential as a way of understanding the history-making of organizations (Foster et al, 2011(Foster et al, , 2017Oertel and Thommes, 2015;Suddaby et al, 2016). The focus here is on the present, which recounts the past instrumentally in ways that suit current needs and strategies, essentially 'revising the past (while thinking in the future perfect tense)' (Gioia et al, 2002: 622).…”
Section: Retrospective Organizational Memorymentioning
confidence: 99%
“…Fiedler & Welpe, 2010;Haunschild et al, 2015), have been focused on identifying how memory practices work within organizations. For example, recent research has demonstrated how memory influences the persistence of organizational identity and identification (Anteby & Molnar, 2012;Foroughi, 2020;Ravasi et al, 2019), the management of change and innovation (Erdogan, Rondi, & De Massis, 2020;Hatch & Schultz, 2017;Foroughi and Al-Amoudi, 2020), the strengthening or weakening of organizational reputation (Foster et al, 2011), and the evisceration of unethical acts (Coraiola & Derry, 2020;Mena et al, 2016). Yet, despite the strength of these works, questions still remain as to the particular boundary conditions that facilitated the operation and impact of Similarly, how does the hierarchical position of actors influence the meaningfulness of their memories for the organization and their impact on organizational memory?…”
Section: Boundary Conditionsmentioning
confidence: 99%
“…These studies maintain that the past is necessarily re-interpreted (e.g. Allen & Brown, 2016; Foster, Suddaby, Minkus, & Wiebe, 2011), including mnemonic traces of the past (Mena et al, 2016) or memory ‘forms’ (Schultz & Hernes, 2013), and that present organizational memories are socially negotiated and often contested (Foroughi, 2020; Ybema, 2014). This perspective also conceptualizes social remembering as processes stemming from social interactions between organizational actors (Rowlinson et al, 2010).…”
Section: An Overview Of Organizational Memory Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Apesar dessas novas concepções sobre a memória, os estudos organizacionais históricos, com poucas exceções (Adorisio, 2014;Foroughi, 2019;Maclean, Harvey, Sillince, & Golant, 2014;Ybema, 2014), parecem se fixar na visão de memória coletada e coletiva proposta por Rowlinson et al (2010). Anteby e Molnar (2012, p. 518, tradução nossa), por exemplo, ao vincularem a literatura de memória coletiva à literatura em identidade organizacional argumentam que o pouco intercâmbio entre as duas seria o fato da última ser "metodologicamente dependente de entrevistas simultaneamente coletadas.…”
Section: A Memória Coletiva Nos Estudos Organizacionaisunclassified